Anthropological view on the history of musical art - Vereshchahina-Biliavska, Olena Ye; Cherkashyna, Olesia V.; Moskvichova, Yuliia O.; Yakymchuk, Olena M.; Lys, Olena V. (Linguistics and Culture Review, 2021)
Research in the field of music anthropology as a separate science began to appear only in the last century. Currently, there are only a small number of studies on musical anthropology in the scientific literature. The purpose of the study is a theoretical generalisation of the manifestations of anthropological thinking in the musical art of classicism, romanticism, and avant-garde, carried out on the basis of contemporary scientific publications. The research methodology is based on the principles of analytical, historical, cultural, and comparative methods, which cover the aspects of musical anthropology of different eras. During the study, the authors considered the manifestations of anthropological thinking in the musical art of classicism, romanticism, and avant-garde, as well as modern scientific publications on musical anthropology. The authors concluded that synthetic, epic-dramatic genres of poetic ballads and poems had a particular influence on the musical composition of the Romantic era. These genres led to the emergence of a number of new compositional structures in the instrumental music of the Romanticism. This study can be used during lectures and practical classes in higher education institutions that specialise in the study of music; it can also be used by students for independent study of musical anthropology.